Achieving Nuclear Ambitions: Scientists, Politicians, and Proliferation - Hymans, Jacques E. C. (Cambridge University Press, 2012)
Despite the global spread of nuclear hardware and knowledge, at least half of the nuclear weapons projects launched since 1970 have definitively failed, and even the successful projects have generally needed far more time than expected. To explain this puzzling slowdown in proliferation, Jacques E. C. Hymans focuses on the relations between politicians and scientific and technical workers in developing countries. By undermining the workers' spirit of professionalism, developing country rulers unintentionally thwart their own nuclear ambitions. Combining rich theoretical analysis, in-depth historical case studies of Iraq, China, Yugoslavia and Argentina and insightful analyses of current-day proliferant states, Achieving Nuclear Ambitions develops a powerful new perspective that effectively counters the widespread fears of a coming cascade of new nuclear powers.